Spectral Properties of Brain Activity Under Two Anesthetics and Their Potential for Inducing Natural Sleep in Birds - Tisdale, Ryan K.; Tieri, Laura; Rattenborg, Niels C.; Beckers, Gabriel J. L.; Lesku, John A. (Frontiers in Neuroscience, 2018)
Both mammals and birds exhibit two sleep states, slow wave sleep (SWS) and rapid eye movement (REM) sleep. Studying certain aspects of sleep-related electrophysiology in freely behaving animals can present numerous methodological constraints, particularly when even fine body movements interfere with electrophysiological signals. Interestingly, under light general anesthesia, mammals and birds also exhibit slow waves similar to those observed during natural SWS. For these reasons, slow waves occurring under general anesthesia are commonly used in the investigation of sleep-related neurophysiology. However, how spectral properties of slow waves induced by anesthesia correspond to those occurring during natural SWS in birds has yet to be investigated systematically. In this study we systematically analyzed spectral properties of electroencephalographic (EEG) patterns of pigeons (Columba livia) occurring under two commonly used anesthetics, isoflurane and urethane. These data were compared with EEG patterns during natural sleep. Slow waves occurring during spontaneous SWS, and those induced with isoflurane and urethane all showed greatest absolute power in the slowest frequencies (< 3 Hz). Isoflurane and urethane-induced slow waves had near-identical power spectra, and both had higher mean power than that observed during SWS for all frequencies examined (0-25 Hz). Interestingly, burst suppression EEG activity observed under deeper planes of isoflurane anesthesia could occur bihemispherically or unihemispherically. Electrophysiological patterns while under isoflurane and urethane share phenomenological and spectral similarities to those occurring during SWS, notably the generation of high amplitude, slow waves and peak low-frequency power. These results build upon other studies which suggest that some anesthetics exert their effects by acting on natural sleep pathways. As such, anesthesia-induced slow waves appear to provide an acceptable model for researchers interested in investigating sleep-related slow waves utilizing electrophysiological methods not suitable for use in freely behaving birds.